Otroška kratka proza Franca Ksaverja Meška in stilna vloga samostalniških manjšalnic - Voršič, Ines (Časopis za zgodovino in narodopisje, 2024)
The article focuses on a selection of short prose, Mladim srcem (1994) (To Young Hearts), which represents children’s and youth oeuvre of Franc Ksaver Meško. From a linguistic perspective, it focuses on nominal diminutives as a noticeable expressive means of expression, which emphasises positive emotionality in particular, e.g. angelček (angel), mamica (mommy), striček (man). The meaning of diminutiveness or hypocorism can be expressed in the names of literary characters, e.g. Peterček, Jakec, and their characterisation, e.g. obrazek (face), ličeca (cheek); modification derivatives with the (hypocoristic) diminutive meaning sometimes reflect modesty, e.g. kočica (house), sobica (room), but at the same time the idyll of the village environment that surrounds the literary heroes, e.g. dolinica (valley), potočič (stream).
Keywords: Besedotvorje; children’s and youth literature; Meško, Franc Ksaver; mladinska književnost; nominal diminutives; otroška književnost; Slovenska mladinska kratka pripovedna proza; word formation